Innovative Diagnostic Techniques for the Preservation of Historical Monuments: Immediate and Instrumental Approaches - Ruben Rodriguez Elizalde (Chemical and Materials Sciences: Developments and Innovations Vol. 9, 2025)
This chapter examines various auscultation techniques used for the conservation and pathological diagnosis of historical monuments and ancient constructions. These structures present technical challenges due to their complexity and fragility, making early and accurate diagnosis essential to prevent significant damage. Inspection techniques are classified into immediate and instrumental methods Immediate methods are based on organoleptic observations or simple tools, and instrumental methods utilize advanced devices for detailed data acquisition. Key immediate techniques include visual inspection, material analysis, and lesion mapping, while instrumental methods encompass thermography, ultrasound, mechanical resistance measurement, and humidity and salt mapping. The innovative use of drones is highlighted as a valuable inspection tool, enabling access to complex areas while minimizing risks to workers and monuments. The chapter emphasizes that these techniques enable faster, less invasive, and more cost-effective interventions, ensuring the preservation of cultural heritage through a preventive approach. It concludes by noting the importance of combining field techniques with laboratory analyses for more comprehensive diagnostics.